2021
DOI: 10.1186/s13018-021-02246-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival and clinical outcomes of non-vascularized autologous and allogeneic fibular grafts are comparable for treating osteonecrosis of the femoral head

Abstract: Background Osteonecrosis of the femoral head (ONFH) is a disabling disease, which often involves young patients. Recently, various hip-preserving surgeries were recommended to delay total hip arthroplasty (THA). Questions/purposes This study aimed to compare clinical outcomes and survival rate in the long-term follow-up between core decompression combined with a non-vascularized autologous fibular graft (group A) and an allogeneic fibular graft (gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…One study compared clinical outcomes and survival rate in the long-term follow-up between non-vascularized autologous fibular graft and an allogeneic fibular graft for the treatment of ONFH [ 21 ]. There is no appreciable difference in the rate of conversion to THA between autologous fibular graft group (12%) and allogeneic fibular graft group.…”
Section: Discussionmentioning
confidence: 99%
“…One study compared clinical outcomes and survival rate in the long-term follow-up between non-vascularized autologous fibular graft and an allogeneic fibular graft for the treatment of ONFH [ 21 ]. There is no appreciable difference in the rate of conversion to THA between autologous fibular graft group (12%) and allogeneic fibular graft group.…”
Section: Discussionmentioning
confidence: 99%
“…Free vascularized fibular grafts for post-traumatic ONFH reportedly resulted in a survival rate of 64% and average HHS of 77.3±24.57 points after a mean follow-up of 10.9 years [ 17 ]. A long-term comparative study of non-vascularized autologous versus allogeneic fibular grafts for ONFH found no significant differences in the HHS (80.3±14.5 and 82.4±13.6 respectively) and survival rate (84.1 and 86% respectively) [ 18 ]. After a mean follow-up of 42 months, the survival rate of a porous tantalum implant combined with bone grafting to treat ONFH was only 52.9%, which shows that this is not a viable option for treating ONFH [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…After sufficiently decompressing the necrotic area of the femoral head using the Advanced Core Decompression introduced in the literature [ 28 ], we used the T-shaped support method in the tunnel theory for reference to provide strong support. A long-term comparative study of allogeneic fibular grafts versus non-vascularized autologous for ONFH found no significant differences in the HHS (82.4 ± 13.6 and 80.3 ± 14.5 respectively) and survival rate (86% and 84.1% respectively) [ 29 ]. Our findings were in agreement with that results.…”
Section: Discussionmentioning
confidence: 99%